(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Libraries play a major role in providing the content required by library users. They encourage and promote learning and understanding knowledge activities. Library users can get lots of books to read and increase their knowledge. In addition, the vast diversity of information means that most people get what they are looking for. Most importantly, libraries are great platforms for making progress. When we get homework in class, the library helps us with reference material. This, in turn, enhances our learning abilities and knowledge. It also helps in our development as a whole. The main objective of this paper is to know the effect of fee-based information on library services. The subjects of this research are users of UPN Veteran Yogyakarta, and the object of this research is library services. The research method used is quantitative method. This research is divided into two levels, namely fee-based information services and the library services. The results show that there are positive and significant results between fee-based information services and the library technical services, and there are positive and significant results between fee-based information services and the library user services.